STRATEGI KOMUNIKASI DALAM PELAYANAN PUBLIK “SIJARLA TERPADU“ DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SOLOK - Elnita' Elnita, Ernita Arif, Asrinaldi (Universitas Riau, 2019)
One of the important things in implementing public services is the ability of a service officer to interact and communicate with the community. One of the communication programs carried out by the Solok Regency government, in this case, is the Department of Population and Civil Registration is to make a communication strategy program that is public service called